The Effect of Financial Difficulties, Company Size Growth on The Change of Public Accountant Offices - Dewi Sutjahyani (Institute of Computer Science (IOCS), 2021)
An auditor has to maintain his independence. To remain this, there are needed to be an auditor shift. Based on PP NO.20 of 2015, the replacement is only applied to auditors, while for KAP there is no more requirement to move to another KAP. White no more restrictions on KAP replacement, it is interseting to examine what factors are considered by the company to keep replacing KAP in the following year? There are at least five factors that are considered by the client to make KAP changes, namely company growth, and financial distress. This research is a type of quantitative research using statistical tools to answer the problem formulation. The population in this study were Consumer Goods companies listed on the Indonesia stock exchange during the period of 2012 to 2016. The result of this study found that company growth, and financial distress had a significant positive effect on KAP..